Pain Coping in Patients With Chronic Migraine and Medication Overuse Headache - Thomas C. van denHoek; Judith A. Pijpers; Erik W. vanZwet; Irene deBoer; Gisela M. Terwindt (Brain and Behavior)
ABSTRACT Background Chronic migraine (CM) is a leading cause of disability and often linked to medication overuse headache (MOH). Psychological factors, such as pain coping, may contribute to chronification and medication overuse. While behavioral therapy can help, identifying patients who will benefit remains challenging. This study compared pain coping in individuals with CM and MOH to those with episodic migraine (EM) and controls without headache. It also assessed whether baseline pain coping in CM patients could predict withdrawal treatment success. Methods In patients that received behavioral therapy as part of the Chronification and Reversibility of Migraine clinical trial, patients with CM and MOH were assessed at baseline and after treatment on pain acceptance with the Acceptance and Action Questionnaire II for Pain (AAQ‐II‐P), and with the Pain‐catastrophizing scale (PCS) and Headache Specific Locus of Control (HSLC) questionnaires. The non‐headache groups were assessed once. In total, 65 CM, 34 EM, and 49 non‐headache controls were included. Results Patients with CM experienced less pain acceptance compared with EM patients and healthy controls with AAQ‐II‐P (adjusted mean difference [AMD]: 10.0 [95% CI: 3.7–16.2], p < 0.001 and AMD: 13.9 [95% CI: 7.8–20.1], p < 0.001, respectively) and had higher PCS (AMD: 12.1 [95% CI: 5.2–19.0], p < 0.001, AMD: 17.3 [95% CI: 10.5—24.0], p < 0.001, respectively), but comparable PCS to patients with back pain or depression. Patients with CM were more likely to believe their headaches were due to coincidence compared to EM, HSLC‐chance (AMD: 4.0 [95% CI: 0.3–7.7], p = 0.034). Importantly, higher PCS scores were associated with greater reduction in migraine days after treatment (OR: 1.06 [95% CI 1.01–1.11], p = 0.030). Conclusions Patients with CM demonstrated poorer pain coping compared to those with EM and healthy controls. High catastrophizing in patients with CM predicts a better response to behavioral withdrawal treatment.